PENGARUH KECERDASAN EMOSI DAN IKLIM SEKOLAH TERHADAP AGRESIVITAS REMAJA - Sari, Yulia Purnama Sari (MOTIVASI, 2016)
ABSTRAKÂ This research was conducted in order to determine empirically the effect of Emotional Intelligence and School Climate to Adolescent Aggressiveness . Aggressiveness is an act of bad form of hurt , curse deliberate by a person against another person. Research conducted on 180 subjects of research at SMPN 5Â  Samarinda using stratified random sampling by distributing a scale of Emotional Intelligence, School Climate and Aggressiveness in SMPN 5 Samarinda, East Kalimantan. Data analyses had been used doubled linear regression analyses technique and used SPSS Statistical 18 for Windows program. Result of the research are shows that there is a significant effect between Emotional Intelligence and School Climate To Aggressiveness in Students of SMPN 5 Samarinda with value of F = 20,344 and p = 0,000. The influence of Emotional Intelligence adn School Climate to Aggressiveness is 18,7% with value of (R2) 0,187. The single influence of Emotional Intelligence to Aggressiveness is 11% while the single influence of School Climate to Aggressiveness is 7,7% . There is a negative relationship between emotional intelligence to the aggressiveness with regression coefficient of -0.359, the lower the emotional intelligence, the higher aggressiveness. Similarly, there is a negative relationship between the School Climate Aggressiveness with regression coefficient of -0.310, the lower (negative) Climate School will be higher as well Aggressiveness.